2019
DOI: 10.12659/msm.918133
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Lymphovascular Invasion in Patients with Stage III Colorectal Cancer: A Retrospective Study

Abstract: Background Lymph node metastasis and tumor progression depend on lymphovascular invasion (LVI). This study aimed to investigate the prognostic role of LVI in patients with stage III colorectal cancer (CRC) and to develop a prognostic nomogram. Material/Methods A retrospective study included 437 patients with stage III CRC. The impact of LVI on overall survival (OS) was analyzed with the Kaplan-Meier method and Cox regression model. A nomogram was constructed, and its pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 29 publications
3
28
0
Order By: Relevance
“…LVI is marked by freely existing malignant cells that seed lymphatic vessels or small veins, having escaped the primary tumor (8). While linked to tumor metastasis/recurrence (and perhaps worse prognosis) and cited as a prognostic factor in various cancers, including those of breast (9) and prostate (10), the impact of LVI on CRC recurrence or prognosis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…LVI is marked by freely existing malignant cells that seed lymphatic vessels or small veins, having escaped the primary tumor (8). While linked to tumor metastasis/recurrence (and perhaps worse prognosis) and cited as a prognostic factor in various cancers, including those of breast (9) and prostate (10), the impact of LVI on CRC recurrence or prognosis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, current practice guidelines suggest that adjuvant chemotherapy was recommended for stage II colon cancer patients with poor prognostic characteristics, including PNI and LVI. Recently, Zhong JW et al revealed that LVI was an indicator of more aggressive biological behavior and a unfavorable prognosis in patients with stage III colorectal cancer [18]. However, there were two limitations to the study by Zhong JW et al that could not con rm the prognostic value of LVI for stage III colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a limited number of studies reported the prognostic value of LVI and PNI in stage III colon cancer [18,19]. In fact, the actual prognostic effect of LVI and PNI remains unclear in stage III colon cancer patients undergoing curative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common malignancy and the fourth leading cause of tumorrelated deaths worldwide [1]. Although advances have been achieved in early detection and effective treatment, the survival rate of CRC is still poor [2].…”
Section: Introductionmentioning
confidence: 99%
“…Lymphovascular invasion (LVI) is de ned as the existence of cancer cells in lymphatics or blood vessels, and is considered to be an early step in lymph node metastasis (Fig. 1a) [1]. Many studies have reported that LVI positivity (LVI +) is a critical prognostic indicator in some cancers, including breast, bladder, and gastric cancers [9][10][11].…”
Section: Introductionmentioning
confidence: 99%